Push or pull? Drivers of female labor force participation during India's economic boom - Stephan Klasen; Janneke Pieters (Institute for the Study of Labor (IZA), 2012)
In the past twenty years, India's economy has grown at increasing rates and now belongs to the fastest-growing economies in the world. This paper examines drivers of female labor force participation in urban India between 1987 and 2004, showing a much more nuanced picture of female labor force participation than one might expect. Recent trends in employment and earnings suggest that at lower levels of education, female labor force participation is driven by necessity rather than economic opportunities. Unit level estimation results confirm that participation of poorly educated women is mainly determined by economic push factors and social status effects. Only at the highest education levels do we see evidence of pull factors drawing women into the labor force at attractive employment and pay conditions. This affects, by 2004, only a small minority of India's women. So despite India's economic boom, it appears that for all but the very well educated, labor market conditions for women have not improved.
urn:nbn:de:101:1-201206146737
Keywords: J21; J22; O12; O15; 330; female labor force participation; education; India; Weibliche Arbeitskräfte; Erwerbstätigkeit; Wirtschaftswachstum; Geschlechterdiskriminierung; Indien